A Making Muffins Using Breakun As A Substitute For Wheat Flour - Agustin, Adela Dwi; Mulyantari, Enny; Prasetyanto, Hermawan (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2024)
Breadfruit (Artocarpus Communis) is a local plant that can be found in various regions of Indonesia and contains many nutrients, but its utilization is still not optimal. One innovation that can be done is by making breadfruit into breadfruit flour, then the breadfruit flour can be used as an ingredient in making snacks in the form of muffins. This is a food diversification program from breadfruit. The method used is quantitative with an experimental type of research. Data collection instruments used organoleptic tests and hedonic tests based on questionnaires with 32 trained respondents to provide consumer responses to muffin products made from breadfruit flour. Next, the data was analyzed quantitatively descriptively. The research results showed the quality of breadfruit flour muffins in terms of color with an average score of 3.38 in the agree category (golden brown). Aspect of aroma with an average score of 3.40 in the agree category (fragrant aroma typical of breadfruit). Taste aspect with an average score of 3.43 in the agree category (sweet, typical of breadfruit). Texture aspect with an average score of 3.31 in the agree (soft) category.